Pelatihan LLS (Language Learning Strategies) Untuk Pelajar Sekolah Menengah Nagari Tanjung Balik, Solok-SUMBAR - Syaifullah; Hamuddin, Budianto; Ahmad, Arif (Indra Institute Research & Publication, 2025)
Based on the results of an interview via WA with one of the vice principals there, he said that our students have not achieved any achievements from English activities or competitions. Likewise, when viewed in daily life or in Teaching and Learning Activities (KBM), their English skills are still very standard. Related to the initial data above, the FADIKSI-UNILAK PKM Team chose the Tanjung Balik village as a partner to be a target in the Tridarma of higher education, especially community service with the title